An Investigation: How Artificial Intelligence can be Used with Supply Chain Management to Improve Business - Kim, Deageon (International Journal of Intelligent Systems and Applications in Engineering, 2023)
The next stage of development for AI and data science is already exhibiting evidence of being successful. While many industries are still trying to cope with the aftereffects of the pandemic, selected businesses have grabbed the opportunity to extensively apply cutting-edge technologies. One of these industries is the supply chain industry. Recent studies indicate that the application of artificial intelligence in supply chains has resulted in increased industrial efficiency, as well as improvements to dynamic logistical systems and real-time delivery management. In this article, the author does a comprehensive review of the relevant previous research in order to evaluate the effects that artificial intelligence (AI) will have on supply chain management (SCM). This research intends to identify the current and potential AI strategies that may enhance both the study and practise of SCM in order to fill the current scientific gap of AI in SCM. These AI strategies may improve both the study and practise of SCM. The following four subjects were given particular attention: the most common AI approaches in supply chain management; the possible Artificial intelligence techniques for employment in supply chain management; the subfields of supply chain management that have already benefited from AI; and the subfields that have a high potential for AI progression. This article provides comprehension by doing thorough research and making synthesis arguments.